Critical Study of the Terms of Reference Used in the Analysis of Striated Muscle. Chemistry and Human Values ​​Standard Methodology - Marchena Basurco, Carlos R. (1962)
In this paper, systematically describes the technology developed in this laboratory for the analysis of skeletal muscle taken as an expression of the cellular phase of the organism, which is a great tool for future research on the changes that would occur in the middle intracellular during various pathological processes, or in many other biological problems. In our particular case, and as part of the curriculum of renal failure, we want to establish, if it, the biochemistry of intracellular environment changes, as with the extracellular environment, or if its composition is more or less independent of renal function.